DYNAMICAL CONSTRAINTS ON KIMBERLITE VOLCANISM - Sparks R.S.J.; Baker L.; Brown R.J.; Schumacher J.; Stripp G.; Walters A.; Field M. (My University, 2006)
Kimberlite volcanism involves the ascent of low viscosity (0.1 to 1 Pa s) and volatile-rich (CO2 and H2O) ultrabasic magmas from depths of 150 km or greater. Theoretical models and empirical evidence suggest ascent along narrow (~1 m) dykes at speeds in the range > 4 to 20 m/s. With typical dyke breadths of 1 to 10 km, magma supply rates are estimated in the range 102 to 105 m3/s with eruption durations of many hours to months. Based on observations, theory and experiments we propose a four-stage model for kimberlite eruptions to explain the main geological relationships of kimberlites. In stage I magma reaches the Earth's surface along fissures and erupts explosively due to their high volatile content. The early flow exit conditions are overpressured with choked flow conditions; an exit velocity of ~200 m/s is estimated as representative. Explosive expansion and near surface overpressures initiate crater and pipe formation from the top downwards. In stage II under-pressures (the difference between the lithostatic pressure and pressure of the erupting mixture) develop within the evolving pipe causing rock bursting at depth, undermining overlying rocks and causing down-faulting and crater rim slumping. Rocks falling into the pipe interior are ejected by the strong explosive flows. Stage II is the erosive stage of pipe formation. As the pipe widens and deepens larger under-pressures develop enhancing pipe wall instability. A critical threshold is reached when the exit pressure falls to one atmosphere. As the pipe widens and deepens further the gas exit velocity declines and ejecta becomes trapped within the pipe, initiating stage III. A fluidised bed of pyroclasts develops within the pipe as the eruption wanes to form typical massive volcaniclastic kimberlite. Marginal breccias represent the transition between stages II and III. After the eruption stage IV is a period of hydrothermal metamorphism (principally serpentinisation) and alteration as the pipe cools and meteoric waters infiltrate the hot pipe fill. Following an eruption an open crater can be filled by kimberlite- and country-rock derived sediments, forming the crater-facies. © 2006 Elsevier B.V. All rights reserved.
Keywords: DIAMONDS; DYNAMICS OF ERUPTIONS; FLUIDISATION; KIMBERLITE